Contrast sensitivity before and after refractive error correction among refractive error patients in Hawassa, Sidama, Ethiopia 2023 - Balcha Negese Kebede; Seid Mohammed Seid; Eyerus Gesesse Samuel (BMC Ophthalmology)
Abstract Background Contrast sensitivity is an important measure of vision quality. Risk of falling injury is strongly associated with poor contrast sensitivity compared with poor near- and distance visual acuity. Since good visual acuity is not necessarily associated with good visual performance in the “real world” it is important to consider contrast sensitivity when prescribing corrective lenses. There is limited evidence on how refractive error and its correction affect contrast sensitivity in the study area. Therefore, this study is important to understand how refractive correction affects contrast sensitivity, which is important baseline information for prescribing refractive error correction. Objective of this study This study aimed to measure the mean difference in contrast sensitivity with and without corrective lenses in patients with refractive error. Methods Objective and subjective refractions were done for each patient, then Pelli- Robson contrast sensitivity was measured for them using computer based Pelli-Robson chart at 1 m. Pelli- Robson contrast sensitivity value (Log CS) with and without corrective lenses were recorded for each study participant. The collected data were checked for completeness and analyzed using SPSS 26. Descriptive analyses, independent sample t-tests, and one-way ANOVA were performed to compare CS means; the findings are presented using tables and pie charts. A P-value of ≤ 0.05 was used to indicate statistical significance. Results One hundred sixty-two patients attending refraction clinics participated in this study with response rate 98.19% of which 51.9% were male. The mean age of the participants was 34.28 ± 12.79 (SD). The mean contrast sensitivity increased from 1.29 ± 0.35 (SD) to1.51 ± 0.28 (SD) LogCS units with refractive correction (p = 0.000). There is no significant difference in contrast sensitivity between the types of refractive errors. Conclusion and recommendation Uncorrected refractive can affect contrast sensitivity; therefore, proper refractive correction is essential to improve visual acuity and contrast sensitivity.